2021
DOI: 10.3390/ijerph18084121
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of a Shorter Treatment Regimen in a Setting with a High Burden of Multidrug-Resistant Tuberculosis

Abstract: Treatment of drug-resistant tuberculosis is lengthy, insufficiently effective, and toxic. Since 2016, the World Health Organization has recommended shorter treatment regimens (STR). We assessed effectiveness and predictors of drug adverse events (DAE) among patients treated with STR. There were 95 consecutive rifampicin-resistant patients enrolled in STR in Tashkent between June 2018 and September 2019. Of these, 66.3% were successfully treated, 17.9% suffered failed treatment, 7.4% died, 5.3% were lost to fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The results showed that the success rate of the short-term treatment regimen was higher than that longer regimen [8]. Many studies have shown a varying success rate of shorter regimen treatment, between 44.3%-83.7% [9][10][11]. Given this varied range of success rate, our study aimed to identify the success rate and factors associated with the outcome of shorter injectable based regimens in MDR-TB patients in West Java province, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the success rate of the short-term treatment regimen was higher than that longer regimen [8]. Many studies have shown a varying success rate of shorter regimen treatment, between 44.3%-83.7% [9][10][11]. Given this varied range of success rate, our study aimed to identify the success rate and factors associated with the outcome of shorter injectable based regimens in MDR-TB patients in West Java province, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Precise identification of such strains demands bacterial confirmation and drug resistance assessment using culture methods, molecular analysis and DNA sequencing [5,6]. Moreover, patients with MDR-TB require intensive treatment for at least nine months (up to 20 months), supported by constant pharmacovigilance to reduce adverse events [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…When used in carefully selected MDR-TB patients who have not been previously exposed to nor have resistance to second-line drugs, these regimens have been reported to achieve relapse-free cures in over 85% of cases, even under programmatic conditions. In 2016, on the basis of data from observational studies of the shorter regimens in different Asian and African countries, the WHO recommended a standardized shorter MDR-TB regimen based on the regimens under study for eligible patients [ 12 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, starting from 2016, Xpert MTB/RIF (a molecular diagnostic assay) has become the first test of choice in all regions of Uzbekistan [ 11 ]. In addition, it is now recommended that patients are considered for chest radiography and mycobacterial culture as part of the diagnostic work-up [ 12 ]. While people with TB are diagnosed and registered in the district TB dispensary, patients can choose between two types of treatment, the inpatient and outpatient modalities, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation